2012
DOI: 10.1007/s00276-011-0928-1
|View full text |Cite
|
Sign up to set email alerts
|

MSCT diagnosis of aneurysms associated with an unusual variant: atypical triplication anterior cerebral artery

Abstract: Atypical triplication anterior cerebral artery is a rare entity and the variation is an important factor leading to aneurysm. A patient with aneurysm that arises from the bifurcation of the distal anterior cerebral arteries is presented. The contralateral anterior cerebral artery is also presented, and there is no communication between the left and the right anterior cerebral artery. The findings from multiple slice CT angiography in this case are illustrated and discussed. The recognition of this variant is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Usually a triple A2 is an incidental finding. Sun et al reported a very interesting case of a triple A2 segment associated with the presence of an aneurysm [ 24 ]. We have not found such a variant in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Usually a triple A2 is an incidental finding. Sun et al reported a very interesting case of a triple A2 segment associated with the presence of an aneurysm [ 24 ]. We have not found such a variant in our study.…”
Section: Discussionmentioning
confidence: 99%
“…7 In some cases the triplication is discussed as a risk factor leading to aneurysm. 15,16 In modern diagnostic algorithms of patients with an acute cerebrovascular event, beyond non-enhanced cerebral CT scans, usually also a CTA is included. CTA is especially inevitable in detecting large vessel occlusions.…”
Section: Discussionmentioning
confidence: 99%
“…Again Cadaveric studies show a vast range of AComA hypoplasia frequency from 9.15 to 30.0% 12 . In addition, aplastic AComA is a rare autopsy finding, found only in 1.8 % of studied subjects [13][14][15][16][17][18] . This phenomenon can be explained by the fact that hypoplastic arteries may not be hemodynamically efficient, therefore are not visible in angiographic studies and thus are considered to be aplastic 19,15 .…”
Section: Discussionmentioning
confidence: 99%